262 Chronic Bowel Perforation Due to Intussusception in an Adult, an Unusual Complication of an Ileocecal Lipoma. (11th January 2018) - Lombardo, Jamie; Lynch, David
Abstract: Intussusception is far more common in children than in adults, and the only recorded cases in the literature of bowel perforation associated with intussusception were due to attempted reduction during surgery and were not longstanding perforations. This case describes a 41-year-old active-duty female patient with abdominal pain for 1 year. She described the pain as sharp spasms lasting 1 to 2 hours, once per week. She also stated that she had a food aversion but no vomiting. She had only been able to ingest a liquid diet for two months prior to presentation and had lost 15 pounds in that time. Radiology identified a transverse colon mass on CT. The surgical specimen was described as intussuscepted ascending and transverse colon. An appendix and short length of ileum were also present. Manual reduction of the intussusception proved impossible as the mass was too large (6 cm). The serosal surface had two prominent defects where the inner loop of intussuscepted colon had perforated through the outer loop of colon, exposing mucosa to the abdominal cavity. Surprisingly, these areas were not inflamed grossly or histologically. The mass was lined by intestinal mucosa and attached to the ileocecal valve by a 2 cm stalk. On histology, the mass was a large lipoma. A search of the literature revealed no reported intussusception cases in adults in which the inner loop of intussuscepted colon perforated through the outer loop and exposed mucosa to the abdominal cavity, essentially forming a chronic bowel perforation. We propose that this is the first reported case and want to make physicians aware that this complication can occur with longstanding intussusception, leaving the patient at increased risk of peritonitis.